Inclusive J production in Z° decays - Dova, María Teresa (1992)
Inclusive J production in Z ° decays is observed via the leptonic decay mode J ~ e + e- (~ = e, #). We measure the branching ratio Br(Z ° ~ J + X) = (4.1 -4- 0.7 (star.) -4- 0.3 (sys.)) × 10 -3. We have calculated the fraction of the J mesons from b-hadron decay and find a branching ratio of B r (b ~ J + X) = (1.3 -4- 0.2 (star.) -4- 0.2 (sys.)) × 10-2. We determine the average fractional energy of bottom hadrons (x e) = 0.70 -4- 0.03 (stat.) -0101 +002 (sys.) using the momentum spectrum of the J mesons. From a study of the angle between the J and the most energetic jet, we set an upper limit on the branching ratio Br(Z ° ~ q/tg*;g* ~ J -F X) < 7.0 × 10 -4 at 90% confidence level.